2021
DOI: 10.36689/uhk/hed/2021-01-009
|View full text |Cite
|
Sign up to set email alerts
|

Sales of Consumer Chemicals in Zero-packaging Stores - a Challenge for Small and Medium-sized Chemical Companies

Abstract: One of the innovations in the area of increasing the sustainability of packaging may be the introduction of zero-packaging sales. The paper deals with the advantages and disadvantages of zero-packaging sales, in relation to consumer chemicals. It presents the results of primary quantitative research carried out with 100 final consumers through electronic surveys using a structured questionnaire. Content analysis and multiple response analysis were used to identify the most significant advantages and disadvanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Bulk dispensers are normally avoided by big retailers, as they require a change in logistics as well as a substantial behavioral change from consumers [12,13]. Nonetheless, the number of small eco-oriented zerowaste stores addressing environmentally conscious costumers surged in the last decade in Europe [14]. A survey by Branska et al [14] showed that frequent costumers of zero-waste stores do not primarily expect lower prices, but rather appreciate the opportunity to buy high quality products and to support local producers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk dispensers are normally avoided by big retailers, as they require a change in logistics as well as a substantial behavioral change from consumers [12,13]. Nonetheless, the number of small eco-oriented zerowaste stores addressing environmentally conscious costumers surged in the last decade in Europe [14]. A survey by Branska et al [14] showed that frequent costumers of zero-waste stores do not primarily expect lower prices, but rather appreciate the opportunity to buy high quality products and to support local producers.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the number of small eco-oriented zerowaste stores addressing environmentally conscious costumers surged in the last decade in Europe [14]. A survey by Branska et al [14] showed that frequent costumers of zero-waste stores do not primarily expect lower prices, but rather appreciate the opportunity to buy high quality products and to support local producers. In this context, zero-waste stores represent a market opportunity for regional producers.…”
Section: Introductionmentioning
confidence: 99%